BMX‐001, a novel redox‐active metalloporphyrin, improves islet function and engraftment in a murine transplant model. Issue 8 (31st March 2018) - Bruni, Antonio; Pepper, Andrew R.; Pawlick, Rena L.; Gala‐Lopez, Boris; Gamble, Anissa; Kin, Tatsuya; Malcolm, Andrew J.; Jones, Carissa; Piganelli, Jon D.; Crapo, James D.; Shapiro, A. M. James
Abstract : Islet transplantation has become a well‐established therapy for select patients with type 1 diabetes. Viability and engraftment can be compromised by the generation of oxidative stress encountered during isolation and culture. We evaluated whether the administration of BMX‐001 (MnTnBuOE‐2‐PyP 5+ [Mn(III) meso ‐tetrakis‐( N ‐b ‐butoxyethylpyridinium‐2‐yl)porphyrin]) and its earlier derivative, BMX‐010 (MnTE‐2‐PyP [Mn(III) meso ‐tetrakis‐( N ‐methylpyridinium‐2‐yl)porphyrin]) could improve islet function and engraftment outcomes. Long‐term culture of human islets with BMX‐001, but not BMX‐010, exhibited preserved in vitro viability. Murine islets isolated and cultured for 24 hours with 34 μmol/L BMX‐001 exhibited improved insulin secretion (n = 3 isolations, P < .05) in response to glucose relative to control islets. In addition, 34 μmol/L BMX‐001–supplemented murine islets exhibited significantly reduced apoptosis as indicated by terminal deoxynucleotidyl transferase dUTP nick end labeling, compared with nontreated control islets ( P < .05). Murine syngeneic islets transplanted under the kidney capsule at a marginal dose of 150 islets revealed 58% of 34 μmol/L BMX‐001–treated islet recipients became euglycemic (n = 11 of 19) compared with 19% of nontreated control islet recipients (n = 3 of 19, P < .05). Of murine recipients receiving a marginal dose of human islets cultured with 34 μmol/L BMX‐001, 92% (n = 12 of 13) achieved euglycemia compared with 57% of control recipients (n = 8 of 14, P = .11). These results demonstrate that the administration of BMX‐001 enhances in vitro viability and augments murine marginal islet mass engraftment. Abstract : Administration of the metalloporphyrin BMX‐001 during pancreas procurement and islet culture improves in vitro islet survival and insulin secretion in response to glucose challenge, and augments islet engraftment in a marginal islet transplant model.